COMPUTATIONAL MECHANICS OF COMBINED PLANAR DEFECTS: EXTRINSIC + INTRINSIC FAULTING IN 3C CLOSE PACKED CRYSTAL STRUCTURES. - ARAGON-FERNANDEZ, BEATRIZ; ESTEVEZ-RAMS, E.; LORA-SERRANO, R.; PENTÓN-MADRIGAL, A. (Revista Cubana de Física, 2018)
Recently, extrinsic faulting has been discussed within the framework of computational mechanics allowing to derive expressions for the statistical complexity, entropy density and excess entropy as a function of faulting probability. In this contribution the analysis is extended to consider the combined presence of two planar faults type within the random faulting model. Extrinsic+intrinsic faults are considered. The ε-machine description of the faulting dynamics is presented. Entropic magnitudes are derived as well as expressions for the hexagonality and the probability of consecutive symbols in the Hägg coding. The analysis continues the study started with individual faulting types under the computational mechanics approach.